USE OF TECHNOLOGY IN LEARNING ARABIC - Masitoh, Dewi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This article examines how technology can be utilized in the Arabic language learning process according to the context faced in various educational institutions. Technology has played an important role in facilitating the language learning process, including Arabic. This can be done with technological developments that contain a lot of information that can be used to improve learning outcomes. This article aims to analyze the benefits of using technology in learning Arabic and its impact on the learning process. Some of the technologies that will be discussed include mobile applications, online learning platforms, and augmented reality. This research will also evaluate the effectiveness of using technology in improving Arabic language skills and learning success